LAND CHANGES AND MANAGEMENT STRATEGIES OF MANGROVE IN SAWO DISTRICT, NORTH NIAS REGENCY, NORTH SUMATERA PROVINCE - Septinus Mendrofa; Rahmat Kurnia; Niken T.M. Pratiwi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
One of the resources that has potential to utilization is a mangrove ecosystem. The aim of this study was to analyze the changes in the area of mangroves, analyze the causes of destruction of mangroves, and formulate strategies for sustainability management of mangroves in Sawo District. The changes in the area of mangroves was identified from imagery and analyzed by ArcGis 10.2.2. The causes of mangrove destruction was analyzed from the data collected from the stakeholders in Sawo District that related to management of mangroves in district level, regency level, and province. The data was analyzed by Analytical Hierarchy Process (AHP) to formulate the strategies for sustainability management of mangroves. The result of landsat imagery showed that, mangrove area has decreased about 17,405 ha within a decade. Mangrove destruction was caused by human activities, such as logging and conversion of mangrove land into agriculture. The main strategy for sustainability management of mangroves was community’s empowerment, then followed by others alternatives. Keywords: AHP, coastal, destruction, ecosystem, landsat